(untitled) (Journal of Pathology of Nepal, 2021)
Introduction: Elevated blood lead level is associated with serious, often irreversible, health consequences. At present, the safe level of blood lead cannot be ascertained since the emerging data indicate the toxic potential to human organ system at a low level that was previously considered safe. Screening for blood lead level is not in regular practice in Nepal. This study is designed to evaluate the prevalence of detectable blood lead level in reproductive age group of Nepalese population that represents the wide local population. Materials and methods: 170 reproductive age group individual (20 to 49 years) attending Samyak diagnostic Pvt Ltd and Alka IVF and fertility centre for regular health checkup were included in this study for blood lead level analysis. The participants were categorized as normal or sub-fertile. Blood lead level was estimated using anodic stripping voltametry. Results: In total study participants, 28.8% of male and 25.8 % of female had BLL ≥3.0 µg/dL. The minimum detectable blood lead level in both male and female was 3.3 µg/dL while the maximum blood lead level was higher in male (15.5 µg/dL) than in female (8.4 µg/dL). The median blood lead level of the sample population was 3.7(4.8 -6.9) µg/dL. There was no significant difference in blood lead level between gender (p=0.108). Conclusion: It is justifiable to screen for blood lead level in the reproductive age group individual in Nepal.